Project Monitoring and Payment System at CV Studio Reka Teknik with a UI UX Approach - Siti Sauda; Ade Kemala Jaya; Muhammad Dandi Permana; Dinda Ayu Ningsih (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The UI/UX (User Interface/User Experience) approach is an initial step in developing a conventional system into a computerized system or developing a computerized system to better suit user needs. In this research, the object raised is CV. Studio Reka Teknik, which is a consulting engineering and general trading service company with the process of conveying information, monitoring and paying for projects, still uses telephone media or meets in person. This causes project monitoring to be impossible in real time and the payment process becomes constrained due to the need to adjust the time to meet between the client and the developer. Therefore, in this research a web-based system was designed by adjusting the needs of the user experience on CV. Studio Reka Teknik. By utilizing the web engineering method, this built web-based system can help and facilitate users in monitoring projects and project payment processes using the system without having to meet directly between the client and the developer. This system will be used on CV. Studio Reka Teknik, which will continue to be monitored for the maintenance and development of this system. After that, if the system is optimal, it can also be applied to other contractor companies.